X-ray characterisation of the basal stacking fault densities of (112̄2) GaN. Issue 35 (9th August 2021) - Pristovsek, Markus; Frentrup, Martin; Zhu, Tongtong; Kusch, Gunnar; Humphreys, Colin J.
Abstract : X-ray diffraction reciprocal space maps in the [1̄21̄0] zone show basal plane stacking (BSF) fold related long diffuse scattering tails along [0001]. The BSF density correlates with the Lorentzian area of the reflection peak. Abstract : The diffuse scattering from basal plane stacking faults (BSF) of (112̄2) GaN layers was observed by laboratory X-ray diffraction (XRD) systems. To observe the diffuse scattering, the (112̄2) GaN samples were oriented in the [1̄21̄0] zone for 101̄ l and 202̄ l series of reflections or in the [4̄51̄0] zone for 213̄ l series. The profiles of the characteristic diffuse intensity streaks (parallel to [0001]) were fitted with a linear combination of area normalised Gauss and Lorentz functions. The area of the Lorentzian contribution correlated with the BSF density measured by cathodoluminescence, electron channeling contrast imaging, and transmission electron microscopy for densities between 10 3 cm −1 to mid 10 5 cm −1, and hence allows for the quantification of the BSF density. The diffuse X-ray scattering of different reflections also suggests that the I 1 type BSFs dominate in our samples. This makes XRD a strong method to quantify BSF densities over the whole range, with the added advantage of being non-destructive.